Lightning protection heat dissipation outdoor distribution box - LI ZHONGLIANG; LU SHUANGJIA; SUN GUOQIANG; WANG JUNXING; LIN XIANHE; LIN XIANPIN (2021)
The utility model discloses a lightning protection heat dissipation outdoor distribution box, which comprises an inner umbrella cover plate, a lightning rod, a conductive wire, a box body, a wiring trough, an exhaust port, an exhaust fan, an air inlet and an air inlet fan. According to the outdoor distribution box, internal devices can be protected under different external conditions, so that electric energy can be stably and safely transmitted. 本实用新型公开了一种防雷散热户外配电箱，包括内伞盖板、避雷针、导电线、箱体、导线槽、排气口、排风扇、进气口和进风扇。本实用新型能够保证户外配电箱在外界不同的条件下能保护内部装置，使电能能够平稳安全的进行输送。